Development and Testing of Intelligent Alcohol Transportation Security System - Velaphi Msomi; Shandene E. A. Solomons (Journal of Advanced Transportation)
The development and testing of intelligent liquid transportation security system are being reported in this paper. The targeted fluid to be secured was ethanol alcohol and this was due to the theft cases occurring during the transportation of this product from the supplier to the customer. The system was developed such that only the radar level sensor (VEGAPULS 62) might be in contact with the fluid and the rest of the system remained outside the liquid carrying container to be secured. The system was developed such that it reports any abnormal liquid level drop through short message service (SMS). The functioning of the developed system was tested through the use of 1040 L Intermediate Bulk Container (IBC) filled with water which was hauled for about 1.5 km. The liquid theft was simulated and the system sent two SMS. The first SMS reported the beginning of water level drop and the second one reported the ending of water level drop. The second SMS reported the amount of liquid that was taken out of the container.